Effects of high-flow oxygen therapy on oxygenation in dogs undergoing diagnostic bronchoscopy - Julia Ortlieb; Hannah Bender; Matthias Schneider; Sabine Tacke; Esther Hassdenteufel (Frontiers in Veterinary Science)
IntroductionHypoxemia is a common complication during bronchoscopy and bronchoalveolar lavage (BAL). High-Flow Oxygen Therapy (HFOT) has been used to improve oxygenation and prevent periods of hypoxemia in people undergoing bronchoscopy.ObjectiveThe main objective of this study was to evaluate the effect of HFOT on oxygenation in dogs undergoing diagnostic bronchoscopy compared to a traditional oxygen supplementation method (TOT). A secondary objective was to assess potential HFOT-related complications.MethodsProspective randomized clinical trial. Dogs presented for diagnostic bronchoscopy were randomly assigned to receive either HFOT or TOT using nasal cannulas during the bronchoscopic procedure. Oxygenation was monitored through PaO2 measurements taken at seven time points: baseline (t0), after preoxygenation (t1), post-induction (t2), pre- and post-BAL sampling (t3 and t4), at the end of the procedure (t5), and 1 h after bronchoscopy (t6). Pre- and post-procedure thoracic radiographs were assessed for air leak syndrome or aerophagia.Results20 privately owned dogs presented for diagnostic bronchoscopy were included in the study (HFOT group: n = 10, TOT group: n = 10). Baseline characteristics and physiological parameters did not differ significantly between groups. Five dogs in each group showed hypoxemia (PaO2 < 80 mmHg) at baseline with 1/5 in each group having PaO2 < 60 mmHg. HFOT improved oxygenation throughout the procedure, with a significant increase in PaO2 observed after preoxygenation (P = 0.001) and at the end of the procedure (P = 0.013). Additionally, only 1/10 dogs in the HFOT group experienced hypoxemia during bronchoscopy compared to 5/10 dogs in the TOT group, and patients in the HFOT achieved numerically higher PaO2 values across all time points during the procedure (t1–t5). No serious adverse events related to HFOT were observed, although aerophagia occurred in both groups without necessitating intervention.ConclusionHFOT can improve oxygenation and prevent episodes of hypoxemia in dogs undergoing bronchoscopy compared to traditional oxygen supplementation methods.